Consultoría para el fortalecimiento del turismo en el municipio de San Agustín - Huila (2021)
This paper begins with the need to improve tourism in the municipality of San Agustín - Huila, to evolve in one of the main economic activities in this territory, which has had a decrease of around 10% in the last year, affecting the hotel businessmen and merchants. For this purpose, a first descriptive stage is carried out, where the critical elements that imply that the municipality is not competitive, as a tourist destination, are observed. Subsequently, a second stage that includes the design of the strategy, which seeks to maintain its current level of visitors, also depends on the increase of more than 50% of the tourists that reach San Agustín in the years to come. To carry out this project, interviews are conducted with merchants from the hotel industry and different parties involved, such as public entities like the Secretaría Municipal de Cultura y Turismo, transporters and Entities of the national order, such as the Agencia Nacional de Infraestructura -ANI-. Based on these and on the review of different official documents, a strategy was generated that has the main interest to increase the number of tourists who visit the municipality, make it more attractive for national and foreign tourists, and, as a final goal, improve the quality of the services to the interior of San Agustín, within the framework of becoming the main economic activity of the municipality above Agriculture, respecting the cultural identity of the municipality and avoiding the overexploitation of natural spaces.